Pengaruh Problem-Based Learning terhadap Hasil Belajar Cerita tentang Daerahku Pada Siswa Kelas IV Sekolah Dasar - Hanifatuffida, Azmi; Yatri, Ika (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on the learning outcomes of fourth-grade students of SDN Ciracas 10 on the material "Stories about My Region". This study uses a quantitative experimental method with a Nonequivalent Control Group Design. The population of this study was all fourth-grade students of SDN Ciracas 10, and the sample consisted of an experimental class (using PBL with Mind Mapping) and a control class (using conventional methods). The sampling technique used purposive sampling, with 60 students as samples. Normality and homogeneity tests were carried out to ensure data suitability. Hypothesis testing using the Paired Sample T-Test showed that there was a significant effect of PBL on student learning outcomes. The results showed that the average post-test score of the experimental class was higher than the control class, which confirmed the effectiveness of PBL in improving student learning outcomes.